Effect of Qingxin Kaiqiao Fang on Hippocampus mRNA Expression of the Inflammation-Related Genes IL-1β, GFAP, and Aβ in an Alzheimer's Disease Rat Model. (18th February 2018) - Mao, Dan-Dan; Yang, Wen-Yu; Li, Yan; Lin, Jian-Wei; Gao, Shi-Yu; Wang, Yi-Ru; Hu, Hai-Yan
Abstract : Objective . To investigate the effects of QKF on expression of amyloid-beta (A β ), interleukin-1 beta (IL-1 β ), and glial fibrillary acidic protein (GFAP) using a rat model of AD. Materials and Methods . Fifty-six male Sprague-Dawley rats were randomly divided into seven groups (eight rats each): control group, sham-operated group, AD model group, groups of AD rats administered with low, medium, and high doses of QKF, and the donepezil group. AD was established by bilateral injection of β -amyloid (A β ) 1–40 into the hippocampus. Two days after AD was established, drugs were administered by gavage. After 14 days of treatment, we used RT-PCR, Western blotting, and immunohistochemistry to measure the transcript expression and protein abundance of A β, IL-1 β, and GFAP, and methenamine silver staining was used to detect amyloid protein particle deposition. Results . Compared to the control group, the rats from the AD model group showed significantly greater expression levels of A β, IL-1 β, and GFAP. However, these differences in expression were abolished by treatment with QKF or donepezil. Conclusion . QKF possesses therapeutic potential against AD because it downregulated A β, IL-1 β, and GFAP in the hippocampus of AD rats. Future studies should further examine the mechanisms through which QKF produces its effects and the consequences of long-term QKF administration.